Effective E-Learning approaches to teaching and learning of Islamic history and civilization in Malaysia and the Muslim World - Salleh, Mohamad Johdi (International Islamic University Malaysia, 2011)
The paper discusses a study on the concept and effective e-learning approaches in the teaching and learning of Islamic History and Civilization in the Integrated Curriculum for Secondary School (ICSS), Malaysia. The study involved about four hundred students from the selected secondary schools in Malaysia. The data were collected through the questionnaires, observation, and interviews. The study discovered that the e-learning method may provide various opportunities to the students in Malaysia to access the enormous Islamic heritage in the Kingdom of Saudi Arabia. This may enhance their knowledge, understanding of the facts, and appreciation of the revealed artifacts and evidences of the truth of Islam. In fact, the e-learning approach is substantially suitable to be used as instructional instrument in distance education at all levels of education, particularly between Malaysia and the Kingdom of Saudi Arabia and other Muslim countries around the world.